GIS-material for the archaeological project: Building plot in the village of Stora Aska - Building site in the village of Stora Aska - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the arcaheological report:
Due to the planned construction of a single-family house, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation in the village of Stora Aska, Slaka parish, Linköping municipality. No prehistoric or medieval features or finds were discovered.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to determine whether the were any archaeological remains on the affected heights and to find a location for the planned house, that would cause as little damage on the potential remains as possible. The aim of the investigation was also to determine the extent and type of the archaeological remains and, if possible, to date them.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har genomfört en arkeologisk förundersökning i Stora Aska by, Slaka socken, Linköpings kommun. Anledningen var planerat uppförande av enbostadshus. Vid förundersökningen hittades inga anläggningar eller fynd som kunde dateras till medeltid eller förhistorisk tid.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att konstatera om det fanns fasta fornlämningar på det aktuella höjdpartiet och att hitta en plats för det planerade huset som gör så lite ingrepp som möjligt på eventuella fornlämningar. Förundersökningen hade även som målsättning att fastställa omfattning och karaktär för äldre lämningar och om möjligt datera dessa.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Tomt i Stora Aska by
Keywords: historical period; historisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi